Ge1-x Mnx Clusters: Central structural and magnetic building blocks of nanoscale wire-like self-assembly in a magnetic semiconductor - Bougeard, D.; Sircar, N.; Ahlers, S.; Lang, V.; Abstreiten, G.; Trampert, A.; Lebeau, J.; Stemmer, S.; Saxey, David; Cerezo, A. (American Chemical Society, 2009)
Controlled nanoscale self-assembly of magnetic entities in semiconductors opens novel perspectives for the tailoring of magnetic semiconductor films and nanostructures with room temperature functionality. We report that a strongly directional self-assembly in growth direction in Mn-alloyed Ge is due to a stacking of individual Ge1-x Mnx clusters. The clusters represent the relevant entitles for the magnetization of the material. They are formed of a core-shell structure displaying a Mn concentration gradient. While the magnetic moments seem to be carried by the shells of the clusters, their core is magnetically inactive. © 2009 American Chemical Society.